High-throughput mapping of brain-wide activity in awake and drug-responsive vertebrates. Issue 3 (19th November 2014) - Lin, Xudong; Wang, Shiqi; Yu, Xudong; Liu, Zhuguo; Wang, Fei; Li, Wai Tsun; Cheng, Shuk Han; Dai, Qiuyun; Shi, Peng
Abstract : A microfluidic system, Fish-Trap, was developed to enable automatic, gel-free, and anesthetic-free immobilization and orientation of zebrafish larvae, allowing high-throughput mapping of drug-induced brain-wide neural activity in awake vertebrates with single-cell resolution. Abstract : The reconstruction of neural activity across complete neural circuits, or brain activity mapping, has great potential in both fundamental and translational neuroscience research. Larval zebrafish, a vertebrate model, has recently been demonstrated to be amenable to whole brain activity mapping in behaving animals. Here we demonstrate a microfluidic array system ("Fish-Trap") that enables high-throughput mapping of brain-wide activity in awake larval zebrafish. Unlike the commonly practiced larva-processing methods using a rigid gel or a capillary tube, which are laborious and time-consuming, the hydrodynamic design of our microfluidic chip allows automatic, gel-free, and anesthetic-free processing of tens of larvae for microscopic imaging with single-cell resolution. Notably, this system provides the capability to directly couple pharmaceutical stimuli with real-time recording of neural activity in a large number of animals, and the local and global effects of pharmacoactive drugs on the nervous system can be directly visualized and evaluated by analyzing drug-induced functional perturbation within or across different brain regions. Using this technology, we tested a set of neurotoxin peptides and obtained new insights into how to exploit neurotoxin derivatives as therapeutic agents. The novel and versatile "Fish-Trap" technology can be readily unitized to study other stimulus (optical, acoustic, or physical) associated functional brain circuits using similar experimental strategies.